1994
DOI: 10.2307/1131311
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' and Parents' Conceptions of Parental Authority and Personal Autonomy

Abstract: Conceptions of parental authority and ratings of adolescent-parent conflict were assessed in 68 sixth, eighth, and tenth graders and their parents. Boundaries of adolescent personal jurisdiction and conflict over these boundaries were examined. Participants judged the legitimacy of parental authority and rated the frequency and intensity of conflict regarding 24 hypothetical moral, conventional, personal, multifaceted (e.g., containing conventional and personal components), prudential, and friendship issues. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
331
7
25

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(404 citation statements)
references
References 13 publications
39
331
7
25
Order By: Relevance
“…Given the apparent importance of legitimacy beliefs for understanding whether or not adolescents facilitate parental monitoring efforts, an expansion of current work (e.g., Darling, Cumsille, & Martínez, 2008;Kuhn & Laird, 2011;Smetana & Asquith, 1994) is needed to understand the origins of these individual differences in adolescents' legitimacy beliefs.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Given the apparent importance of legitimacy beliefs for understanding whether or not adolescents facilitate parental monitoring efforts, an expansion of current work (e.g., Darling, Cumsille, & Martínez, 2008;Kuhn & Laird, 2011;Smetana & Asquith, 1994) is needed to understand the origins of these individual differences in adolescents' legitimacy beliefs.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…We find parents' decisions about whether to "buzz off" or "butt in" compelling (Brown, 1996), especially given the developmental overlay of adolescents' desire for more connection to peers and less dependence on parents. Parents who are too heavy-handed may infringe on what adolescents perceive as their legitimate purview (Smetana & Asquith, 1994), whereas parents who are minimally involved may increase susceptibility to negative peer influence (Steinberg, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Given the normative increase in deviant behavior during this age period, virtually all early adolescents are exposed to significant levels of problematic behavior within their broader peer groups (Moffitt, 1993), even though most teens acknowledge and respect the values their parents hold regarding such behavior (Smetana & Asquith, 1994). Research has now shown that among youth who have been identified as at risk for delinquent behavior, peers can strongly support the development of each other's deviance in part by entraining one another in deviant behavior patterns (Dishion, Poulin, & Burraston, 2001;Dishion, Spracklen, Andrews, & Patterson, 1996).…”
mentioning
confidence: 99%